DESIGN LEARNING ABOUT REFLECTION WITH PMRI APPROACH IN CLASS VII - Firdaus, Firdaus; Hartono, Yusuf; Somakim, Somakim (Sriwijaya University Learning and Education International Conference, 2018)
In the process of learning about reflection, some teachers teach the concept of reflection in an abstract way. As a result students have difficulty in understanding the concept transformation of reflection. This study aims to build students' understanding of the reverse context of "AMBULANCE" and to design the learning path of reflection learning in class VII with PMRI approach. Before the learning process first designed learning tool that is in the form of Ice berg, Hypothetical Learning Trajectory (HLT), syllabus, Lesson Plan and Student Activity Sheet. This reflective learning involves four activities: observing the context, identifying reflecting properties with an inverted 'AMBULANCE' writing context, drawing the letters reflected in the reversed "AMBULANCE" and determining the result of point and wake reflection on the Cartesian plane. From the learning result shows that by using the context of writing "AMBULANCE" is reversed, able to build students' understanding and give opportunity to students to understand the concept of reflection and produce trajectory of learning about reflection in the form of learning process path or learning experience passed by students.